Mental Health Screening in Child Justice Systems: a Comparison between Malaysia and Selected Jurisdictions - Chong, Edwyn Seng Yau; Abdul Aziz, Mohammad Firdaus; Thambapillay, Sridevi (UUM PRESS, 2024)
Mental health is an important aspect at every stage of life, from childhood to adolescence and to old age. It is crucial to people’s overall well-being. In various studies that have been conducted, it has been found that a significant number of child offenders experienced some form of mental health problem or issue. This awareness has led to many countries adopting mental health screening as a part of the admission procedure into juvenile institutions. It has been argued that such a practice can benefit child offenders as it not only allows for the early detection of any underlying mental health issues but also assists the relevant authorities in personalising rehabilitation programmes that are unique for each child offender. Little is known about the regulatory approach taken by Malaysia and whether or not the existing practice, if any, is in line with other experienced jurisdictions at the international level. Hence, this article examines the laws and policies regarding mental health screening for child offenders admitted into juvenile institutions in Malaysia with a comparison made with other selected jurisdictions namely the United States of America, New Zealand, and the Netherlands. This study found that significant differences exist between Malaysia and selected jurisdictions such as the timing of mental health screening or the mental health screening tools utilised, and therefore, proposes some measures that can be learned and adopted by Malaysia to improve its child justice system and ensure the well-being of child offenders admitted into juvenile institutions